Penerapan Penilaian Beracuan Norma Oleh Guru Untuk Mengetahui Tingkat Pencapaian Hasil Belajar Siswa Secara Kelompok Dan Klasikal Pada Pelajaran Seni Budaya Kelas X SMA Negeri 2 Koto XI Tarusan - Irfandi Agusta Putra; Yos Sudarman (Jurnal Kajian dan Penelitian Umum, 2023)
This study aims to explain the implementation of norm-based assessments by teachers in the assessment of cultural arts (music) learning outcomes of Class X students of SMA Negeri 2 Koto XI Tarusan and explain that teachers can determine the level of achievement of student learning outcomes in groups and classically in cultural arts (music) lessons of students at school. This research uses a type of qualitative research with a descriptive method of analysis. The results showed that the teacher's efforts in determining the achievement of student learning outcomes in groups and classically based on the results of the UH1, UH-2 and UTS Arts and Culture exams in grades X-1 to X-4 at SMA Negeri 2 Koto XI Tarusan seemed successful. The teacher can explain how he can know and at the same time determine the final assessment results (in letters A, B, C, and D) as a grouping of high, medium and low scores on student exam results using the reference to the difference between individual averages and class averages. The teacher has explained that if the greater the individual average score difference with the class average, then students can be classified into groups of high-ability students and vice versa. While the completeness and incompleteness of the achievement of learning outcomes known from exam results can be determined on the difference in individual averages above 0 or below.